2016
DOI: 10.1021/acs.jpclett.6b00249
|View full text |Cite
|
Sign up to set email alerts
|

Application of 119Sn CPMG MAS NMR for Fast Characterization of Sn Sites in Zeolites with Natural 119Sn Isotope Abundance

Abstract: (119)Sn CPMG MAS NMR is demonstrated to be a fast and efficient method for characterization of Sn-sites in Sn-containing zeolites. Tuning of the CPMG echo-train sequence decreases the experimental time by a factor of 5-40 in the case of as-synthesized and hydrated Sn-BEA samples and by 3 orders of magnitude in the case of dehydrated Sn-BEA samples as compared to conventional methods. In the latter case, the reconstruction of the quantitative spectrum without the loss of sensitivity is shown to be possible. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
74
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(78 citation statements)
references
References 35 publications
(69 reference statements)
3
74
0
Order By: Relevance
“…[37][38] In line with recent developments, spectra were recorded by Carr-Purcell-Meiboom-Gill (CPMG) echo-train acquisition methods, as exemplified by the Ivanova group. 39,40 Due to the signal enhancements made possibly by CPMG methods, spectra could be recorded on materials containing naturally abundant quantities of Sn. All ex reactor samples were measured without prior heat treatment, in order to preserve integrity of the samples following operation, and were thus compared to fresh samples also in their hydrated forms.…”
Section: Resultsmentioning
confidence: 99%
“…[37][38] In line with recent developments, spectra were recorded by Carr-Purcell-Meiboom-Gill (CPMG) echo-train acquisition methods, as exemplified by the Ivanova group. 39,40 Due to the signal enhancements made possibly by CPMG methods, spectra could be recorded on materials containing naturally abundant quantities of Sn. All ex reactor samples were measured without prior heat treatment, in order to preserve integrity of the samples following operation, and were thus compared to fresh samples also in their hydrated forms.…”
Section: Resultsmentioning
confidence: 99%
“…31,35 Recently, Ivanova et al showed that other methods could be used to obtain enhanced signals with unlabeled samples. 36 Other metals of interest, including Ti, Zr, and Hf, suffer from extreme challenges in NMR sensitivity that stem from low natural abundance, large quadrupolar moment, and/or low gyromagnetic ratios (as shown in Table S1). 37 …”
Section: Introductionmentioning
confidence: 99%
“…Recent work aimed at elucidating the catalytic functioning of Sn-Beta includes DFT calculations, FT-IR, TPR and 119 Sn-NMR spectroscopy. [39][40][41][42][43][44] Despite it being a crystalline material, the preparation method oen greatly inuences the catalytic performance. Two principally different preparation methods are normally used, direct synthesis under hydrothermal conditions using hydrouoric acid as mineralising agent [Sn-Beta (HT)] and synthesis by post treatment of a dealuminated Beta zeolite with a tin source [Sn-Beta (PT)].…”
Section: Introductionmentioning
confidence: 99%